Effect of Neodymium and Transition Metals Co-doped on Structural, Optical and Magnetic Properties of BiFeO3 Materials - Thang, Dao Viet; Thao, Du Thi Xuan; Oanh, Le Thi Mai; Minh, Nguyen Van (VNU Journal of Science: Mathematics - Physics, 2015)
Structural, optical and magnetic properties of BiFeO 3 and Bi 0.9 Nd 0.1 Fe 0.95 TM 0.05 O 3 (TM = Ni, Co) polycrystallines prepared by sol–gel method have been investigated. X-ray diffraction (XRD) patterns reveal that all samples crystalize in rhombohedrally distorted perovskite structure belonging to R 3C space group. The analysis results of both XRD and Raman scattering show the increase of lattice distortion with the co-replacing of Nd and TM ions into A and B sites respectively. All samples exhibit a weak ferromagnetic behavior at room temperature with the enhancement of the magnetization  in Nd and TM co-doped samples. Keywords: Raman, co-doped, magnetization, BFO.